Electrochemical sensor based on polyaniline / tin dioxide / carbon nanobelt as well as preparation method and application of electrochemical sensor
By modifying the electrodes with polyaniline/tin dioxide nano/carbon nanobelt-based electrochemical sensors, the problems of complex sample pretreatment and high detection cost in the detection of drug residues in the prior art are solved, and the effects of simple operation, rapid detection and high sensitivity are achieved.
Patent Information
- Application Number
- CN202510067302.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art has problems such as complex pre-processing of samples, time-consuming and laborious, high detection costs and high operation requirements when detecting drug residues, making it difficult to achieve low-cost, simple operation, rapid detection and high sensitivity detection effects.
Polyaniline/tin dioxide nano/carbon nanoribbon-based electrochemical sensor is used to modify the glass carbon electrode by combining the carbon nanoribbon with the polyaniline/tin dioxide nanomaterial to form a composite electrode to detect drug residues in milk and ambient water bodies.
It realizes the detection effect of simple operation, large specific surface area, fast electrical signal response, and no complex sample pretreatment, while maintaining high detection sensitivity, good selectivity and anti-interference ability.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a polyaniline / tin dioxide / carbon nanobelt-based electrochemical sensor and a method for simultaneously detecting three drug residues of acetaminophen (AP), sulfadiazine (SD) and trimethoprim (TMP) in milk and environmental water using the same, belonging to the technical field of chemically modified electrodes and drug electrochemical analysis. Background Art
[0002] Carbon nanotubes (CNTs) are a special type of carbon material with great development prospects. They have been widely studied and applied due to their unique electronic structure and excellent electrical and mechanical properties. However, the original CNTs have a large aspect ratio, which makes them very easy to accumulate into clusters. At the same time, due to the sealing of the two ends of CNTs, their specific surface area is relatively small. In addition, the original CNTs have low surface energy and are often chemically inert. These structural deficiencies greatly limit their related electrochemical applications. Therefore, it is necessary to modify the original carbon nanotubes to overcome the inherent structural defects of CNTs. Chemical oxidation is usually used to modify CNTs. The carbon nanobelts (CNBs) obtained by oxidation cutting not only effectively increase their specific surface area, but also inhibit the agglomeration and accumulation of carbon tubes to a certain extent. However, due to the introduction of a large number of oxygen-containing groups into the surface of carbon tubes, some of the CNTs sp 2 The structure of the type is destroyed, which has a certain negative impact on its original excellent conductive properties. Therefore, it is necessary to combine with other materials to improve this shortcoming.
[0003] In recent years, with the rapid development of industry, agriculture and urbanization, coupled with a variety of human activities that have a negative impact on the environment, environmental pollution, especially water pollution, has occurred. Harmful pollutants in water, especially various drug pollutants, are destroying the balance of the aquatic environment at an alarming rate, increasing environmental toxicity, and ultimately posing a serious threat to human health, production and safety through the transmission of the food chain. On the other hand, there are many types of drug residues in the environment or food, usually at trace levels, with complex composition and structure, resulting in difficulties in sample enrichment and matrix effect interference in analysis and detection.
[0004] At present, people have developed many analytical methods for detecting drug residues, such as spectrophotometry, high performance liquid chromatography (HPLC), high performance liquid phase tandem mass spectrometry (HPLC-MS / MS), fluorescence analysis, capillary electrophoresis, etc. However, they generally have some disadvantages: (1) the sample pretreatment process is complicated, time-consuming and labor-intensive, and the detection cost is high; (2) the operator has high requirements and needs to master good instrument analysis theory and operation skills. Therefore, it is necessary to develop new technologies with low cost, simple sample preparation, short detection time, low detection limit and easy operation.
[0005] The present invention constructs a polyaniline / tin dioxide nano / carbon nanobelt-based electrochemical sensor, which has the advantages of simple operation, large specific surface area, fast electrical signal response, no need for complex sample pretreatment, etc., compared with the above methods, while maintaining high detection sensitivity. The present invention uses carbon nanobelt (CNB) as the substrate material, functionalizes it through polyaniline / tin dioxide nanomaterial (PAN / SnO2), and uses a drop coating method to fix the composite material to the surface of the glassy carbon electrode to obtain a polyaniline / tin dioxide nano / carbon nanobelt-based electrochemical sensor, which has been successfully applied to the simultaneous detection of three drug residues of acetaminophen, sulfadiazine and trimethoprim in environmental water and milk. Summary of the invention
[0006] In order to solve the shortcomings of the above-mentioned technology, the present invention provides a preparation and application method of a polyaniline / tin dioxide nano / carbon nanobelt-based electrochemical sensor.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: preparation of polyaniline / tin dioxide nano / carbon nanobelt-based electrochemical sensor, the preparation method comprising the following steps: (1) Preparation of carbon nanobelt (CNB): Synthesize carbon nanobelt by modified Hummers method, disperse a certain mass of multi-walled carbon nanotubes and sodium nitrate in sulfuric acid solution, stir in ice bath for a period of time, slowly add a certain amount of potassium permanganate, heat for reaction for a period of time, add a certain volume of H2O2 after cooling to room temperature, centrifuge and wash the obtained solid to dry, and obtain carbon nanobelt (CNB). (2) Preparation of polyaniline / tin dioxide nanocomposite (PAN / SnO2): Prepare nano-tin oxide (SnO2) by sol-gel method, take a certain amount of prepared nano-tin dioxide and aniline monomers and ultrasonically disperse them in hydrochloric acid solution, drop an appropriate amount of potassium persulfate in ice bath, stir continuously, wash and dry the obtained product, and obtain PAN / SnO2 composite. (3) Preparation of polyaniline / tin dioxide / carbon nanobelt composite (PAN / SnO2 / CNB): weigh the carbon nanobelt and PAN / SnO2 composite in a certain proportion in a beaker, disperse them evenly and mix them, and after ultrasonic reaction for a certain period of time, centrifuge and freeze-dry the product to obtain a polyaniline / tin dioxide / carbon nanobelt composite. (4) Preparation of PAN / SnO2 / CNB composite modified electrode: prepare a uniform suspension of the prepared PAN / SnO2 / CNB composite using dilute acetic acid as solvent and chitosan as binder, and fix a certain amount of the above dispersion on the surface of glassy carbon electrode (GCE) by drop coating method, and dry it naturally at room temperature to obtain a PAN / SnO2 / CNB composite modified electrode (PAN / SnO2 / CNB / GCE).
[0008] Furthermore, in the step (1), the amount of carbon nanotubes used is 1 g, the amount of sodium nitrite used is 0.5 g, the amount of sulfuric acid (98%) used is 50 mL, the amount of potassium permanganate used is 5 g, and the amount of H2O2 (30%) used is 5 mL; the oxidation reaction conditions are: reaction at 40°C for 2 hours; and the drying conditions are drying at 60°C for more than 12 hours.
[0009] Furthermore, in the step (2), the amount of nano-tin oxide used is 0.25 g, the amount of aniline monomer used is 0.5 g, the amount of potassium persulfate and hydrochloric acid used is 0.1 mol / L, 50 mL; the polymerization conditions are: ice bath reaction for 24 hours; freeze drying for 24 hours.
[0010] Furthermore, in step (3), the amount of carbon nanobelt used is 2 mg, the amount of polyaniline / tin dioxide used is 48 mg, and the liquid phase reaction conditions are: ultrasonic reaction at room temperature for 2.5 hours.
[0011] Furthermore, the freeze-drying in steps (1) and (2) is performed for 24 hours.
[0012] Furthermore, in step (4), the volume of the PAN / SnO2 / CNB composite dispersion is 10 μL, and the concentration is 0.2 mg / mL.
[0013] The invention discloses an application of a polyaniline / tin dioxide nano / carbon nanobelt-based electrochemical sensor, which is applied to the simultaneous determination of three drug residues, namely, acetaminophen, sulfadiazine and trimethoprim, in environmental water or milk: (I) a three-electrode system is formed by using the prepared modified electrode PAN / SnO2 / CNB / GCE as a working electrode, a platinum electrode as a counter electrode, and a silver / silver chloride electrode as a reference electrode, and the three-electrode system is placed in a PBS buffer solution; (II) the electrochemical behaviors of acetaminophen (AP), sulfadiazine (SD) and trimethoprim (TMP) on the modified electrode PAN / SnO2 / CNB / GCE are studied by using cyclic voltammetry, differential voltammetry and electrochemical impedance spectroscopy; (III) the contents of acetaminophen (AP), sulfadiazine (SD) and trimethoprim (TMP) in environmental water or milk samples, as well as the spike recovery rate, are analyzed and detected by differential voltammetry.
[0014] Furthermore, the three-electrode system constructed in step I is placed in a 0.05 mol / L PBS buffer solution at pH=7.0.
[0015] Furthermore, in step II, the electrochemical behaviors of acetaminophen (AP), sulfadiazine (SD), and trimethoprim (TMP) on the modified electrode PAN / SnO2 / CNB / GCE were studied: the CV scan rate was 50 mV / s; the DPV amplitude was 0.05 V, and the potential increment was 0.004 V; the initial frequency Init E(V) of EIS was -0.23 V, the amplitude was 0.005 V, and the rest time was 2 s.
[0016] Further, in step III: the environmental water sample or milk sample is centrifuged to obtain the supernatant, which is diluted with a 0.05 mol / L PBS buffer solution at pH=7.0 at a ratio of 1:10 for later use.
[0017] The present invention modifies the electrode with a polyaniline / tin dioxide / carbon nanobelt composite material, which effectively increases the surface area and conductivity of the electrode, and significantly improves the sensing performance of the electrode. Experimental results show that the PAN / SnO2 / CNB / GCE modified electrode can be used for the simultaneous determination of three drug residues of acetaminophen, sulfadiazine, and trimethoprim. The operation is simple, rapid, sensitive, and has good selectivity and excellent anti-interference ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Different nanomaterials of the present invention: nano tin dioxide (A), polyaniline (B), carbon nanobelts (C), SEM images of polyaniline / tin dioxide (D) and polyaniline / tin dioxide / carbon nanobelt composites (E), and polyaniline / tin dioxide / carbon nanobelt EDS spectra (F); Figure 2 FTIR spectra (A) and XRD (B) of different nanomaterials of the present invention: tin dioxide, polyaniline, carbon nanobelts and polyaniline / tin dioxide / carbon nanobelt composites; Figure 3 Cyclic voltammetry curves CV (A), differential voltammetry curves DPV (B), and electrochemical impedance spectroscopy (EIS) (C) of different working electrodes: bare electrode, tin dioxide, polyaniline, carbon nanobelt, polyaniline / tin dioxide / carbon nanobelt composite modified electrode in 1 mmol / L K3[Fe(CN)6] and 0.2 mol / L KNO3 mixed solution; Figure 4 (A) is the DPV curve of polyaniline / tin dioxide / carbon nanobelt modified electrode under different concentrations of acetaminophen; (B) is the oxidation peak current I pa (C) is the DPV curve of polyaniline / tin dioxide / carbon nanobelt modified electrode under different concentrations of sulfadiazine; (D) is the oxidation peak current I pa(E) is the DPV curve of polyaniline / tin dioxide / carbon nanobelt modified electrode under different concentrations of trimethoprim; (F) is the oxidation peak current I pa The relationship curve between the concentration of trimethoprim and the concentration of chloramphenicol. DETAILED DESCRIPTION
[0019] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby. Example 1
[0020] Preparation of polyaniline / tin dioxide / carbon nanobelt-based electrochemical sensor, the specific preparation steps are as follows: (1) Preparation of carbon nanobelt (CNB): Carbon nanobelt was synthesized by modified Hummers method. First, 1 g MWCNTs and 0.5 g sodium nitrate were dispersed in a round-bottom flask containing 46 mL concentrated sulfuric acid (98%). Then, the mixture was stirred in an ice bath for half an hour, and then 5 g potassium permanganate was slowly added under strong stirring. After the addition was completed, the ice bath was removed, and then the reaction was carried out at 40 °C for 2 hours. After the reaction was completed, 100 mL of water was slowly added under strong stirring. After the solution was cooled to room temperature, 5 mL of H2O2 (mass fraction 30%) was added. The obtained solution was centrifuged and washed several times with ethanol and deionized water until the pH of the centrifuged suspension was close to 7. Finally, the obtained product was transferred to a vacuum drying oven and dried at 60 °C overnight to obtain carbon nanobelt (CNB). (2) Preparation of polyaniline / tin dioxide nanocomposite (PAN / SnO2): First, light yellow nanotin oxide (SnO2) was prepared by sol-gel method. Then, 0.25 g of the prepared nanotin dioxide and 0.5 g of aniline monomer were ultrasonically dispersed in 50 mL of 0.1 mol / L hydrochloric acid solution. 50 mL of 0.1 mol / L potassium persulfate was added dropwise in an ice bath. The mixture was stirred continuously and reacted for 24 h. The obtained product was washed with deionized water and freeze-dried for 24 h to obtain a dark green PAN / SnO2 nanocomposite. The product was stored at room temperature for later use. (3) Preparation of polyaniline / tin dioxide / carbon nanobelt composite (PAN / SnO2 / CNB): 2 mg of carbon nanobelt and 48 mg of PAN / SnO2 composite were weighed and dispersed in deionized water respectively. After mixing and ultrasonic reaction for 2.5 h, the product was centrifuged and freeze-dried for 24 h to obtain PAN / SnO2 / CNB composite. (4) Preparation of PAN / SnO2 / CNB composite modified electrode: 2 mg of PAN / SnO2 / CNB composite was dispersed in a pre-prepared acetic acid / chitosan (mass fraction 20:1) mixed solution and ultrasonicated for 2 h to obtain a uniform suspension with a concentration of 0.2 mg / mL. 10 μL of the above dispersion was fixed on the surface of glassy carbon electrode (GCE) by drop coating and naturally dried at room temperature to obtain PAN / SnO2 / CNB composite modified electrode (PAN / SnO2 / CNB / GCE). Example 2
[0021] like Figure 1As shown in the figure: the surface morphology of PANI and SnO2 is similar, both showing a relatively evenly distributed spherical particle structure. The shape of the CNB prepared by the present invention is a strip shape with two ends open. The reason is that the oxidation longitudinal cutting causes the original carbon nanotube structure to be cut open, and the surface is relatively smooth with obvious wrinkles. On the PAN / SnO2 / CNB nanocomposite material, it is clearly seen that the PANI and SnO2 nanoparticles are evenly dispersed on the curled and wrinkled CNB ribbon structure, which makes the composite material have a larger specific surface area. Example 3
[0022] The PAN / SnO2 / CNB composite material prepared in Example 1 was subjected to Fourier infrared spectroscopy and X-ray diffractometer analysis. Figure 2 As shown in the infrared spectrum, the SnO2 -1 and 1628 cm -1 A broad peak appeared at 3413 cm-1, corresponding to the O-Sn-O symmetric and antisymmetric vibration modes and the OH stretching mode, respectively. The successful oxidative polymerization of aniline monomer is associated with the appearance of two peaks, at 3413 cm-1. -1 and 1127 cm -1 In the spectrum of CNB, 1634 cm -1 and 1081cm -1 The two peaks at are attributed to the bending vibration and strong CC vibration of the carbon skeleton. XRD spectrum analysis shows that tin dioxide has diffraction peaks at 2θ = 26.5°, 33.8°, 37.9°, 51.8°, 54.8°, 57.9°, 61.9°, 66.1°, 71.4°, 75.2° and 78.7°, polyaniline has two peaks at 20.7° and 25°, and carbon nanobelts have characteristic peaks at 26.4° and 42.3°. The PANI / SnO2 / CNB composite has characteristic peaks corresponding to the components of CNB, PANI and SnO2, but the peak intensity may be reduced due to some intermolecular forces, which fully indicates that the electrode material has been successfully composited. Example 4
[0023] The electrochemical behavior of the PAN / SnO2 / CNB-based electrochemical sensor prepared in Example 1 was characterized by cyclic voltammetry, differential pulse voltammetry and impedance spectroscopy. Figure 3As shown in A and B, the cyclic voltammetry (CV) and differential pulse voltammetry (DPV) curves of different working electrodes GCE, SnO2 / GCE, PAN / GCE, CNB / GCE, PAN / SnO2 / GCE, and PAN / SnO2 / CNB / GCE in 1 mmol / L K3[Fe(CN)6] and 0.2 mol / LKNO3 mixed solution. It can be seen that compared with the bare glassy carbon electrode GCE, SnO2 / GCE, and PAN / GCE modified electrodes, the anodic current and cathodic current of the PAN / SnO2 / CNB composite modified electrode are significantly enhanced, and the peak current reaches the highest, indicating that CNB has high electrocatalytic activity and excellent conductivity. After PAN / SnO2 is composited with CNB, the current intensity is further improved, indicating that the transfer rate of surface electrons is improved through synergistic effects between the PAN / SnO2 / CNB composite materials. Figure 3 C is the electrochemical impedance spectroscopy (EIS) curves (EIS) measured by different working electrodes in 5 mmol / L K3[Fe(CN)6] / K4[Fe(CN)6] 0.2 mol / L KCl solution expressed as Nyquist plots. Figure 3 As can be seen from Figure C, the resistance of the bare electrode is 1216 Ω, the resistance of the electrode modified with the PAN / SnO2 composite material is 593 Ω, and the resistance of the electrode modified with the PAN / SnO2 / CNB is 403 Ω, which is significantly lower than that of PAN / SnO2. This proves that CNB has excellent conductivity and its addition greatly promotes the transfer of electrons on the electrode surface. This result is consistent with the results obtained from the above cyclic voltammetry test (CV), indicating that the PAN / SnO2 / CNB composite material has been successfully synthesized. Example 5
[0024] Under the optimal experimental conditions, the DPV curves of acetaminophen, sulfadiazine and trimethoprim at different concentrations were measured using the polyaniline / tin dioxide / carbon nanobelt composite modified electrode prepared in Example 1. The oxidation peak current values were recorded respectively, and the corresponding standard curves were plotted. The results are shown in FIG. Figure 4 As shown. Figure 4 It can be seen from A and D that the detection potential of AP is about 0.36 V. In the range of 5 to 1000 μM, the AP concentration and the peak current show a certain linear relationship, and the linear equation is I p (μA)=0.0686C AP (μM)+2.2873, the correlation coefficient is 0.9880, and the detection limit is 0.18 μM. Figure 4As can be seen from B and E, the detection potential of SD is about 0.8 V. The experiment found that in the concentration range of 5 to 1000 μM, the SD concentration and the peak current showed a good linear relationship, and the linear equation was Ip (μA) = 0.0439C SD (μM)+1.2938, the correlation coefficient is 0.991, and the detection limit is 0.13 μM. Figure 4 As can be seen from C and F, the detection potential of TMP is about 1.08 V. In the concentration range of 5-500 μM, the linear relationship between TMP concentration and peak current is as follows: Ip(μA)=0.0349C TMP (μM)+1.5121, the correlation coefficient is 0.996, and the detection limit is 2.67 μM. The experimental results show that the polyaniline / tin dioxide / carbon nanobelt-based electrochemical sensor provided by the present invention is successfully applied to the simultaneous detection of acetaminophen, sulfadiazine and trimethoprim, and has a wide detection range and a low detection limit, as well as good selectivity and anti-interference ability. Example 6
[0025] In order to detect the practicality of the PAN / SnO2 / CNB composite modified electrode, the polyaniline / tin dioxide / carbon nanobelt-based electrochemical sensor prepared in Example 1 was applied to the detection of AP, SD and TMP content in commercial milk and environmental water samples. Packaged milk was purchased from a local supermarket, and actual sampling was carried out in the waters of Nanhu Lake in Yueyang City. The actual water samples and milk were first centrifuged and filtered, and then diluted with PBS buffer solution with pH = 7.0 at a volume ratio of 10:1. DPV detection was carried out, and standard recovery tests for AP, SD and TMP were carried out to determine the recovery rate. The results are shown in Table 1.
[0026] Table 1. Detection of AP, SD and TMP by PAN / SnO2 / CNB modified electrode in real samples
[0027] This method was applied to the determination of three drug residues, AP, SD and TMP, in commercial milk and environmental water samples. The recovery rates in the sample spike recovery test could reach 90.8%~108.0%, and the results were quite satisfactory.
[0028] The above implementation modes are not limitations of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the scope of the technical solution of the present invention also belong to the protection scope of the present invention.
Claims
1. A method for preparing an electrochemical sensor based on a polyaniline / tin dioxide / carbon nanobelt composite material, characterized in that: The method comprises the following steps: (1) preparing carbon nanobelts (CNB): synthesizing carbon nanobelts by using a modified Hummers method, dispersing a certain amount of multi-walled carbon nanotubes and sodium nitrate in a sulfuric acid solution, stirring in an ice bath for a period of time, slowly adding a certain amount of potassium permanganate, heating for a period of time, and adding a certain volume of H2O2 after cooling to room temperature, washing the obtained solid by centrifugation, and drying to obtain carbon nanobelts (CNB). (2) preparing polyaniline / tin dioxide nanocomposite (PAN / SnO2): preparing nanotin oxide (SnO2) by a sol-gel method, taking a certain amount of the obtained nanotin dioxide and aniline monomers and ultrasonically dispersing them in a hydrochloric acid solution, dropping an appropriate amount of potassium persulfate in an ice bath, stirring continuously, washing and drying the obtained product, and obtaining a PAN / SnO2 composite. (3) Preparation of polyaniline / tin dioxide / carbon nanobelt composite (PAN / SnO2 / CNB): weigh the carbon nanobelt and PAN / SnO2 composite in a certain proportion in a beaker, disperse them evenly and mix them, and after ultrasonic reaction for a certain period of time, centrifuge and freeze-dry the product to obtain a polyaniline / tin dioxide / carbon nanobelt composite. (4) Preparation of PAN / SnO2 / CNB composite modified electrode: prepare a uniform suspension of the prepared PAN / SnO2 / CNB composite using dilute acetic acid as solvent and chitosan as binder, and drop a certain amount of the above dispersion on the surface of the glassy carbon electrode (GCE) by drop coating, and dry it naturally at room temperature to obtain a PAN / SnO2 / CNB composite modified electrode (PAN / SnO2 / CNB / GCE).
2. The preparation of the polyaniline / tin dioxide / carbon nanobelt electrochemical sensor according to claim 1, characterized in that: In the step (1), 1 g of carbon nanotubes, 0.5 g of sodium nitrite, 50 mL of sulfuric acid (98%), 5 g of potassium permanganate, and 5 mL of H2O2 (30%) are used; the oxidation reaction conditions are: reaction at 40°C for 2 hours; and the drying conditions are drying at 60°C for more than 12 hours.
3. The preparation of the polyaniline / tin dioxide / carbon nanobelt electrochemical sensor according to claim 1, characterized in that: In the step (2), the amount of nano-tin oxide used is 0.25 g, the amount of aniline monomer used is 0.5 g, and the amount of potassium persulfate and hydrochloric acid used is 0.1 mol / L, 50 mL; polymerization conditions: ice bath reaction for 24 hours; freeze drying for 24 hours.
4. The preparation of the polyaniline / tin dioxide / carbon nanobelt electrochemical sensor according to claim 1, characterized in that: In the step (3), the amount of carbon nanobelt used is 2 mg, the amount of polyaniline / tin dioxide used is 48 mg, and the liquid phase reaction conditions are: continuous stirring and reaction for 2.5 hours at room temperature.
5. The preparation of the polyaniline / tin dioxide / carbon nanobelt electrochemical sensor according to claim 1, characterized in that: The freeze drying in steps (1) and (2) is performed for 24 hours.
6. The preparation of the polyaniline / tin dioxide / carbon nanobelt electrochemical sensor according to claim 1, characterized in that: The volume of the PAN / SnO2 / CNB composite dispersion in step (4) is 10 μL, and the concentration is 0.2 mg / mL.
7. An application of a polyaniline / tin dioxide / carbon nanobelt electrochemical sensor prepared by claim 1, characterized in that: The electrochemical sensor is successfully applied to the simultaneous detection of three drug residues of acetaminophen (AP), sulfadiazine (SD) and trimethoprim (TMP) in environmental water or milk samples, mainly comprising the following steps: (I) The prepared modified electrode PAN / SnO2 / CNB / GCE was used as the working electrode, the platinum electrode as the counter electrode, and the silver / silver chloride electrode as the reference electrode to form a three-electrode system, which was placed in PBS buffer solution; (II) The electrochemical behaviors of acetaminophen (AP), sulfadiazine (SD), and trimethoprim (TMP) on the modified electrode PAN / SnO2 / CNB / GCE were studied by cyclic voltammetry, differential voltammetry, and electrochemical impedance spectroscopy; (III) The contents of acetaminophen (AP), sulfadiazine (SD), and trimethoprim (TMP) in environmental water or milk samples were detected by differential voltammetry, as well as the spiked recovery rate.
8. The application of the polyaniline / tin dioxide / carbon nanobelt electrochemical sensor prepared in claim 7, characterized in that: In the step (I), the concentration of PBS is 0.05 mol / L, and the pH is 7.
0.
9. The application of the polyaniline / tin dioxide / carbon nanobelt electrochemical sensor prepared in claim 7, characterized in that: In the step (II), the CV scan rate is 50 mV / s; the DPV amplitude is 0.05 V, and the potential increment is 0.004 V; the initial frequency Init E(V) of EIS is -0.23 V, the amplitude is 0.005 V, and the rest time is 2 s.
10. The application of the polyaniline / tin dioxide / carbon nanobelt electrochemical sensor prepared in claim 7, characterized in that: In the step (III): the environmental water sample or milk sample is centrifuged to obtain the supernatant, which is diluted with a 0.05 mol / L PBS buffer solution with a pH of 7.0 at a ratio of 1:10 for later use.